Long-Lasting Oscillations in the Electro-Oxidation of Formic Acid on PtSn Intermetallic Surfaces - Perini, Nickson; Batista, Bruno C.; Angelo, Antonio C. D. [UNESP]; Epstein, Irving R.; Varela, Hamilton (Wiley-Blackwell, 2014)
Even when in contact with virtually infinite reservoirs, natural and manmade oscillators typically drift in phase space on a time-scale considerably slower than that of the intrinsic oscillator. A ubiquitous example is the inexorable aging process experienced by all living systems. Typical electrocatalytic reactions under oscillatory conditions oscillate for only a few dozen stable cycles due to slow surface poisoning that ultimately results in destruction of the limit cycle. We report the observation of unprecedented long-lasting temporal oscillations in the electro-oxidation of formic acid on an ordered intermetallic PtSn phase. The introduction of Sn substantially increases the catalytic activity and retards the irreversible surface oxidation, which results in the stabilization of more than 2200 oscillatory cycles in about 40 h; a 30-40-fold stabilization with respect to the behavior of pure Pt surfaces. The dynamics were modeled and numerical simulations point to the surface processes underlying the high stability.
Keywords: electrocatalysis; formic acid; kinetics; platinum; tin